The Circular RNA Cdr1as Act as an Oncogene in Hepatocellular Carcinoma through Targeting miR-7 Expression - Yu, Lei; Gong, Xuejun; Sun, Lei; Zhou, Qiying; Lu, Baoling; Zhu, Liying (PloS one, 2016)
CircRNAs are a class of endogenous RNA that regulates gene expression at the post-transcriptional or transcriptionallevel through interacting with other molecules or microRNAs. Increasing studies have demonstrated that circRNAs play a crucial role in biology processes. CircRNAs are proved as potentialbiomarkers in many diseases including cancers. However, the role of Cdr1as in Hepatocellular carcinoma (HCC) remains to be elucidated. We demonstrated that Cdr1as expression was upregulated in HCC tissues compared with the adjacent non-tumor tissues. In addtion, miR-7 expression was downregulated in HCC tissues compared with the adjacent non-tumor tissues. Moreover, the expression level of miR-7 was inversely correlated with that in HCC tissues. Knockdown of Cdr1as suppressed the HCC cell proliferation and invasion. Overexpression of miR-7 inhibited the HCC cell proliferation and invasion. Overexpression of miR-7 could suppress the direct target gene CCNE1 and PIK3CD expression. Knockdown of Cdr1as suppressed the expression of miR-7 and also inhibited the CCNE1 and PIK3CD expression. Furthermore, knockdown of Cdr1as suppressed the HCC cell proliferation and invasion through targeting miR-7. These data suggested that Cdr1as acted as an oncogene partly through targeting miR-7 in HCC.